KONSEP DAN STRATEGI PENDIDIKAN KARAKTER DI SEKOLAH DALAM PENGEMBANGAN KURIKULUM 2013 - Mardia Harahap, Ainun (IAIN Padangsidimpuan, 2016)
Character of Education is a form of human activity in which there is action intended for educating the next generation, by forming individual self-improvement continuously and Â they practice themselves in order towards a better life. School institutions, good principals, teachers and all school staff and employees are required to be able to create a school culture that can support the formation of good character for students. Especially teachers are expected to develop positive potential possessed by the students, so that students have a good character. Society, parents and other community members should advocates for the formation of the student's character, to get good behavior, good culture, so that the entire student life is inseparable from the process of habituation and the formation of good character.